Dampak PSAK 30 Terhadap Laporan Keuangan Perusahaan di Indonesia - Fitri Sulistianti; Sondang Mariani Rajagukguk (Jurnal Akuntansi, 2011)
This research investigates the influence of PSAK 30 on the financial report in Indonesia companies. The change in PSAK 30 (R2007) that originally was rule based become principle based, the change in classification from operating lease to finance lease. The impact of this change caused the change in the treatment of lease account of entity. The researcher carried out the lease capitalization simulation and its impact on the Balance, Income Statement of companies in Indonesia. The sample of this research consisted of 20 companies that were registered in Indonesian Stock Exchange that had the obligation lease and assets lease. The researcher gathered the data from OSIRIS for year 2006 and 2007 and compares the change in several financial ratios. The researcher hypothesized that adoption PSAK 30 gave the impact on financial report. Results of the research showed 1) the increasing in three variables of the income measurements that is the earning before the income of the tax and depreciation (EBITDA), the income from the operation, as well as the earning per share (EPS) as the impact of operating lease capitalization 2) increasing in weighted assets, the decreasing in weighted liabilities and decreasing in financial leverage 3) the increase in the amortizes cost and interest expense as well as the reduction in the rent expense. The conclusion is, PSAK 30 gave an important impact on financial report and decreasing the distortion in financial report.Keywords : PSAK 30, off-Balance Sheet, on-Balance Sheet, Lease